Questionnaire Method in Marketing Research - Abdurashitova Sh. A.; Muyassarova M. M. (Scholars Digest Publishing, 2023)
The topic of this article is relevant at the present time, because Surveys are currently a very popular method of collecting marketing information, and the data obtained during the survey allows us to reduce the degree of uncertainty associated with making marketing decisions.
Keywords: questionnaire, marketing research, questions, structural plan of the questionnaire, market.